Personal data security as a form of legal certainty for the fulfillment of consumer rights for online loans - Kerti, N.G.N. Renti Maharaini (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Online lending services in Indonesia have grown rapidly in recent years, but this has also brought great challenges regarding the protection of consumers' personal data. Personal data security has become a very important issue, given the many cases of data breaches that can harm consumers. This study aims to analyse the role of personal data security in the fulfilment of consumer rights in online lending services, as well as to evaluate the existing legal certainty related to consumer personal data protection. The method used in this research is empirical juridical, with an analytical approach to relevant legal regulations and case studies regarding data breaches in online lending services. The results show that although there are regulations governing personal data protection, implementation is still weak and faces challenges such as a lack of consumer digital literacy and supervision of illegal service providers. The conclusion of this study is that legal certainty is needed to protect consumer rights, and that stricter regulations and better supervision of online loan service providers are essential. The implications of this research are the need for strengthened regulation, increased supervision by the Financial Services Authority (OJK) and other relevant institutions, and education to consumers on their rights regarding personal data.